Women career development phases: drivers influencing Malaysian married professional women’s decisions to stay or leave the workforce - Ling, Lim Wee; Mohd Rasdi, Roziah (Springer Nature, 2024)
Career decisions among women in different developmental stages are more complicated than the men’s career. Women’s career decisions vary at different career development stages due to their personal, family, and other drivers embedded throughout their life. The objectives of this study are to clarify the variation of career decisions and the drivers affecting Malaysian married professional women’s career decisions at early, mid and late career stages. The three-phase model of career development by O’Neil and Bilimoria and Kaleidoscope Career Model by Sullivan and Mainiero were integrated in this study. A quantitative approach was employed by collecting data among 236 married professional women based on these three distinct groups via online survey questionnaires. Descriptive statistics were tested using SPSS whereas proposed hypotheses were analyzed using Partial Least Square Structural Equation Modelling. The descriptive analysis revealed that young married professional women had higher intention to leave the workforce. Family supportiveness organizational perception is found to be the most significant driver influencing the married professional women’s career decisions at all three career stages. From the practical lens, the results of this study will help human resource practitioners develop appropriate talent retention strategies and policies to minimize the talent drain phenomenon among elite women group in Malaysia.